Formulasi Sirup Analgesik Ekstrak Etanol Daun Songgolangit (Tridax procumbens L.) - Tompunu, Citra; Edy, Hosea Jaya; Supriati, Hamidah Sri (PHARMACON, 2013)
ABSTRACTThe aims of this research were to testing the quality of songgolangit leaves ethanol extractanalgesic syrup. Songgolangit leaves ethanol extract analgesic syrup were make with 3various concentrations of active substances which are 40%, 50%, 60% and the quality weretesting. The outcome of quality testing of songgolangit leaves ethanol extract syrup has agood homogeneity. On organoleptic test, songgolangit leaves ethanol extract syrup wassmelling like extract, has a bitter taste, and colored yellow. The pH of songgolangit leavesethanol extract syrup be on the maximum stability which are on 5-7 pH. The average ofcastings time be on the similliar values with the positif control that become a parameter.Key words : analgesic, Tridax procumbens L.